Interessengeleitetes Studium. Eine niveaudeskriptorenorientierte Neukonzeption religionswissenschaftlicher Einfuhrungsseminare - JOHANNSEN, DIRK (University of Berne, 2009)
The thesis includes the development and evaluation of revised introductory courses on the study of religion adjusted to the Bologna framework. In the first chapter, we define the general competencies to be obtained in the course of the study as well as the teaching outcomes for specific courses according to the Swiss national qualification framework (nqf.ch HS). Subsequently, we identify the concrete teaching aims for the level of the organization of each single teaching unit. In chapter two, we develop suitable teaching tools and student tasks, aiming at intense student participation and fostering a self-directed learning process. Chapter three presents different support measures for supervising individual students. Chapter four outlines different forms of assessment, aiming at maximum transparency and guidance throughout the learning process. The course structure, as outlined in the thesis, was tested in 2007 and 2008 at the University of Fribourg. Chapter five contains the evaluation and suggests improvements. Chapter six includes a revised tool for designing student-centered and transparent courses.
PUBLISHED
Keywords: University didactics; Qualification frameworks; Qualification frameworks in the study of religion